EFFECTS OF GROUNDNUT (ARACHIS HYPOGEA L) VARIETIES ON THE FLAVOUR PROFILE AND CONSUMER ACCEPTABILITY OF DAKUWA (A CEREAL-GROUNDNUT BASED SNACK) - Oladele, Adekanmi Kamar; Sogunle, Kazeem A. (FUDMA JOURNAL OF SCIENCES, 2020)
The quality of Dakuwa can be affected by raw materials and processing methods. This work studied the effects of groundnut (Arachis hypogea L.) varieties (Campala, white and Sere) on the colour, flavour profile and sensory properties of Dakuwa. The flavour profile of the Dakuwa samples was analysed with gas chromatography – mass spectroscopy (GC – MS), colour by chroma meter and proximate composition using standard methods while sensory evaluation was done by 25 untrained panelists. The results were analysed using one way analysis of variance. Dakuwa sample with Campala groundnut (DKWC) had the highest concentration of alcohols (20 μg /100 g), aldehydes (86 μg /100 g), ketones (1.9 μg /100 g), heterocyclic aromatic compounds (11.2 μg /100 g), and total flavour compounds (151 μg /100 g) suggesting higher lipid oxidation and Maillard reaction compared to Dakuwa with Sere and White groundnuts. DKWC had significantly lower L* (lightness) value and significantly higher browning index (84.75) suggesting a higher browning reaction compared to other samples. Sensory evaluation results indicated no significant (p > 0.05) difference in the samples. It can be concluded that any of the three groundnut varieties can be used to produce Dakuwa without altering its sensory qualities.